Expectations about insulin therapy, perceived insulin‐delivery system social acceptability, and insulin treatment satisfaction contribute to decreases in insulin therapy self‐efficacy in patients with type 2 diabetes after 36 weeks insulin therapy (2型糖尿病患者经过36周的胰岛素治疗后，患者对胰岛素治疗的期望、感知的胰岛素给药装置的社会接受性以及对胰岛素治疗的满意度都可以导致胰岛素治疗自我效能感的下降)1. (28th May 2013) - Hayes, Risa P.; Curtis, Bradley; Ilag, Liza; Nelson, David R.; Wong, Mayme; Funnell, Martha
Abstract Background Self‐efficacy plays a critical role in diabetes self‐care. Herein we explore factors contributing to decreased insulin therapy self‐efficacy in insulin‐naïve patients with type 2 diabetes mellitus (T2DM) initiating and managing insulin therapy over 36 weeks. Methods The study was conducted within an international, randomized clinical trial comparing two insulin therapies administered by insulin pen in patients with T2DM inadequately controlled with oral antihyperglycemic medications. Patients completed the Self‐Efficacy about Insulin Therapy Questionnaire (SEITQ) at baseline and endpoint. Patients also completed patient‐reported measures assessing expectations about insulin therapy at baseline and perceptions about insulin therapy and insulin‐delivery system (IDS) satisfaction at endpoint. Baseline and endpoint SEITQ scores were compared. Using prespecified criteria, patients were classified as having "decreased" or "no change/improved" insulin self‐efficacy. Demographic, clinical, and patient‐reported variables were entered into a logistic regression model with decreased insulin self‐efficacy (yes or no) as the dependent variable. Results Baseline and endpoint SEITQ data were available for 450 insulin‐naïve T2DM patients (mean age 59 years; 53% female; 57% Caucasian; mean baseline HbA1c 9.4%; 80.0 mmol/mol). Insulin therapy self‐efficacy improved from baseline to endpoint (74.0 vs 77.5; P < 0.001). Logistic regression analysis indicated that lower IDS satisfaction (P < 0.0001), lower IDS social acceptability (P = 0.004), and more positive expectations of insulin therapy (P < 0.0001) were associated with decreased insulin self‐efficacy. Conclusions A candid discussion between clinicians and their insulin‐naïve T2DM patients about the benefits and challenges of insulin therapy may prevent unrealistic expectations that could potentially undermine insulin self‐efficacy.